Mapping of Preeclampsia and Hemorrhage Complications in Pregnant Women with Maternal Mortality Rates in East Java Province - Aisyah Hanifa Chaerani Putri; Lutfi Fajar Nuraidah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Maternal mortality remains a public health issue in many countries, including Indonesia. Preeclampsia and hemorrhage are complications during pregnancy that are two of the three leading causes of maternal mortality in Indonesia and East Java Province. This study aims to map the prevalence of preeclampsia and hemorrhage in pregnant women with maternal mortality rates in East Java Province in 2024. This study is an observational cross-sectional study using secondary data on the number of cases of preeclampsia and hemorrhage complications in pregnant women and the total number of maternal deaths in 38 districts/cities in East Java Province in 2023. The analysis was performed using the QGIS application and Pearson and Spearman correlation tests. The highest maternal mortality rates were concentrated in the eastern part of East Java Province. Most of the prevalence of preeclampsia in pregnant women was spread across areas with high maternal mortality rates, while the prevalence of hemorrhage in pregnant women was spread randomly across several areas regardless of the high or low maternal mortality rates. The Pearson correlation test showed a moderate correlation between the prevalence of preeclampsia and maternal mortality rates. The Spearman correlation test showed no correlation between the prevalence of hemorrhage in pregnant women and maternal mortality rates with a weak correlation that was not statistically significant. The statistically and spatially significant variations indicate that other factors contribute to the pattern of maternal mortality in East Java Province. There is a need for strategies to optimize pregnancy check-ups as a measure for early detection of pregnancy complications in order to reduce the risk of delayed treatment, which can result in maternal mortality.